Prison Mental Health In-reach: The Effect of Open Referral Pathways. Issue 1 (2nd January 2017) - Hopkin, Gareth; Samele, Chiara; Singh, Karan; Craig, Tom; Valmaggia, Lucia; Forrester, Andrew
Abstract : In England and Wales, mental health in-reach teams manage high levels of mental disorder in prisons, but problems with reception screening and referral triage have been identified. As one potential solution, we examined the effect of an open referral pathway upon one in-reach team by evaluating its referrals and caseload across two time periods (in 2008 and 2011). There was a doubling of team referrals (from 101 to 203) with significantly improved identification of people with no mental health history. There was further evidence for a lowering of thresholds for referral and assessment, an approach that can be seen as helpful within a system that is known to under-identify mental health problems. Despite limitations, this evaluation offers some evidence for the effectiveness of open referral systems. It also raises questions about the potential effects of liaison and diversion services that are presently being piloted for national introduction.